Optimization of the direct synthesis of dimethyl ether from CO2 rich synthesis gas: closing the loop between experimental investigations and model-based reactor design - Delgado Otalvaro, Nirvana; Kaiser, Markus; Delgado, Karla Herrera; Wild, Stefan; Sauer, Joerg; Freund, Hannsjörg (Reaction Chemistry & Engineering, 2020)
Reaction kinetic modeling, model-based optimization and experimental validation are performed for the direct synthesis of dimethyl ether from CO2 rich synthesis gas. Among these disciplines, experimental methods and models are aligned in a stringent way of action, i.e., the same setup and models are applied throughout the whole contribution. First, a lumped reaction kinetic model from the literature is modified and parametrized to fit a vast array of 240 data points measured in a laboratory fixed bed reactor. The data were acquired using a mechanical mixture of the commercial catalysts CuO/ZnO/Al2O3 and gamma-Al2O3. For this setup, a predictive model is derived and applied within dynamic model-based optimization. Here, the single-pass COx conversion serves as objective function while the operating conditions and composition of the mixed catalyst bed are the optimization variables. Finally, the optimization results obtained numerically are validated experimentally verifying the identified performance enhancement qualitatively. The remaining quantitative deviations yield valuable insights into model and methodological weaknesses or inaccuracies, closing the loop between kinetic investigations, model-based optimization and experimental validation.
CRIS-Team WoS Importer:2020-05-29